(untitled) (Global Journal of Medical Research, 2022)
Introduction Hypertensive disorders are among the most common medical disorders during pregnancy and continue to be a serious challenge in obstetric practice Aims This study investigated the various risk factors fetal and maternal outcome in cases of preeclampsia Study Design This was a cross sectional study conducted over a period from January 2019 and June 2020 This study enrolled 100 cases of non severe preeclampsia and 100 cases of severe preeclampsia Methods and Materials Participants were selected by consecutive sampling and baseline data were collected by using a predesigned and pretested structured questionnaire Data Analysis Data were entered and analysed by using SPSS version 20 Results It was observed that preeclampsia was more common in the age group of 21 to 30 years 68 women living in rural area 71 5 low socioeconomic class unbooked antenatal history 70 Maximum number of patients were Primigravida 52 5 79 5 were anemic 50 patients had vaginal delivery 50 had Caesarean section 73 5 babies born were full term alive babies preterm were 20 5 41 4 8 IUD and 2 4 stillbirth Early neonatal death occurred in 4 5 babies 9 26 52 babies were low birth weight 18 5 were Growth restricted 5 5 babies had Neonatal jaundice and 18 5 babies were admitted in Neonatal Intensive Care Unit The most common maternal complication was Post Partum Haemorrhage 7 5 which was observed in 15 cases the next common complication was Abruption which occurred in 10 cases 5 Maternal mortality occurred in 2 cases 1 Conclusion This study concludes that fetal and maternal outcome were markedly affected by preeclampsia and also the grave complications were more common in severe preeclampsia cases than in non severe preeclampsia cases So proper Antenatal care early diagnosis of preeclampsia and timely intervention will decrease perinatal morbidity and mortality